Regulation of Pfh1 helicase activity by nucleic acid interactions and mitochondrial SSB - María Ortiz-Rodríguez; Saurabh P. Singh; Francisco J. Cao-García; Roberto Galletto; Borja Ibarra (Proceedings of the National Academy of Sciences, 2026)
Pif1-family helicases are essential for proper nuclear and mitochondrial genome maintenance, yet the regulation of their activities remains incompletely understood. Here, we use single-molecule manipulation and visualization techniques to dissect the real-time mechanochemical behavior of Pfh1, the sole Pif1-family helicase in Schizosaccharomyces pombe. We systematically varied force, ATP concentration, fork composition, and the single-stranded DNA–binding protein spRim1, to quantify the unwinding and single-stranded DNA translocation properties of Pfh1. We find that Pfh1 operates through unwinding-rewinding cycles during which coordinated interactions with both DNA strands at the fork optimize ATP utilization. Contacts with the translocating strand modulate ATP affinity, while interactions with the displaced strand control maximum unwinding velocity. Binding of spRim1 to the displaced strand disrupts the latter interactions, increasing the unwinding velocity. Stable interactions of the helicase with both strands at the fork may limit unwinding processivity to ~20 bp, eventually triggering transition to rewinding. Rewinding proceeds through an ATP-dependent process that is incompatible with strand switching, in which ATP turnover modulates DNA contacts and rewinding rate. Binding of spRim1 to the displaced strand further accelerates rewinding, possibly by competing with helicase–DNA interactions, and facilitates recovery of the active unwinding conformation once the fork has rewound. Together, these findings suggest that Pfh1 balances unwinding and rewinding through coordinated ATP-dependent strand interactions, providing insight into how Pif1-family helicases are controlled at replication forks.